Dichotomy in duration and severity of acute inflammatory responses in humans arising from differentially expressed proresolution pathways - Morris, Thea (National Academy of Sciences, 2010)
Lipoxins (Lxs) and aspirin-triggered epi-Lxs (15-epi-LxA(4)) act through the ALX/FPRL1 receptor to block leukocyte trafficking, dampen cytokine/chemokine synthesis, and enhance phagocytic clearance of apoptotic leukocytes—key requisites for inflammatory resolution. Although studies using primarily inbred rodents have highlighted resolution as an active event, little is known about the role resolution pathways play in controlling the duration/profile of inflammatory responses in humans. To examine this, we found two types of responders to cantharidin-induced skin blisters in male healthy volunteers: those with immediate leukocyte accumulation and cytokine/chemokine synthesis followed by early resolution and a second group whose inflammation increased gradually over time followed by delayed resolution. In early resolvers, blister 15-epi-LxA(4) and leukocyte ALX were low, but increased as inflammation abated. In contrast, in delayed resolvers, 15-epi-LxA(4) and ALX were high early in the response but waned as inflammation progressed. Elevating 15-epi-LxA(4) in early resolvers using aspirin increased blister leukocyte ALX but reduced cytokines/chemokines as well as polymorphonuclear leukocyte and macrophage numbers. These findings show that two phenotypes exist in humans with respect to inflammation severity/longevity controlled by proresolution mediators, namely 15-epi-LxA(4). These data have implications for understanding the etiology of chronic inflammation and future directions in antiinflammatory therapy.